2014
DOI: 10.5301/jva.5000318
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Subclavian Venipuncture is More Rapidly Learned than the Anatomic Landmark Technique in Simulation Training

Abstract: US-SV was learned more quickly than LM-SV in a simulation model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Our study further corroborated the effectiveness of CCUS through models/simulations, strengthening training effects, and promoting the widespread application of bedside ultrasound. Traditional teaching relies mainly on instructor lectures, with students learning via textbooks and notes and then practicing on existing patients, which is a highly random process [20]. In contrast, simulation protects patient safety and rights, reducing hospital-acquired infection risk from repeated student practice.…”
Section: Discussionmentioning
confidence: 99%
“…Our study further corroborated the effectiveness of CCUS through models/simulations, strengthening training effects, and promoting the widespread application of bedside ultrasound. Traditional teaching relies mainly on instructor lectures, with students learning via textbooks and notes and then practicing on existing patients, which is a highly random process [20]. In contrast, simulation protects patient safety and rights, reducing hospital-acquired infection risk from repeated student practice.…”
Section: Discussionmentioning
confidence: 99%
“…The value of simulation education in learning the technique of ultrasound‐guided placement of central venous catheters has been shown in simulation studies . In fact, it has been shown that the ultrasound guided technique is easier for trainees to learn than the anatomical landmark method, through simulation studies …”
Section: Simulation Education In Acute Medicine and Surgerymentioning
confidence: 99%
“… 21 This approach offers a shorter, more direct course to the SCV, traversing only fascial planes, whereas with an infraclavicular approach, it must traverse the pectoralis major muscle, which may lead to increased catheter malpositioning. 22 , 23 In a randomized prospective comparative study of infraclavicular vs. supraclavicular approaches using a LM technique, there was a 9% incidence of catheter malpositioning in the infraclavicular group compared to 0.5% in the supraclavicular group. 22 In another prospective comparative study evaluating 144 patients requiring central venous catheterization, a supraclavicular approach had a statistically significant higher success rate in comparison to an infraclavicular approach.…”
Section: Supraclavicular Subclavian Vein Cannulation Under Ultrasoundmentioning
confidence: 99%
“…In a study by Tokumine et al, 20 medical trainees received instruction on both LM and US-guided SCV cannulation using the longitudinal axis. 23 Sufficient skill to place an US-guided SCV catheter was achieved with three attempts compared to nine for the LM technique.…”
Section: Infraclavicular Subclavian Cannulation Under Ultrasound Guidmentioning
confidence: 99%